The sword unbound - Ryder-Hanrahan, Gareth (Ryder-Hanrahan, Gareth. Lands of the firstborn, 2024)
"Twenty years ago, Alf and his companions defeated the Dark Lord and claimed his city. Now, those few of the Nine that remain find themselves unwilling rebels, defying the authority of both the mortal Lords they once served and the immortal king of the elves - the secret architect of everything they've ever known. Once lauded as a mighty hero, Alf is now labelled a traitor and hunted by the very gods he seeks to bring down. As desperate rebellion blazes across the land, Alf seeks the right path through a maze of conspiracy, wielding a weapon of evil. The black sword Spellbreaker has found its purpose in these dark days. But can Aelfric remain a hero, or is his legend tarnished forever?" --